2014
DOI: 10.1016/j.bjan.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Complicação anestésica em hospital de reabilitação. A incidência tem relação com a consulta pré‐anestésica?

Abstract: Patients with more impaired physical status (American Society of Anaesthesiology 3 and 4), with airway disease, tumor or parenchymal disease, diabetes or disorder of lipid metabolism, thyroid disease, former smokers and very prolonged anesthetic acts present a higher risk of anesthesia-related complications. Therefore, they should be actively investigated in the pre-anesthetic evaluation consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…This reduction ranged from 28.8% for ECG to 89.6% for PT/aPTT. When analyzing only the exams done by the PG group, we found that 22.4% of 21,22 .…”
mentioning
confidence: 92%
“…This reduction ranged from 28.8% for ECG to 89.6% for PT/aPTT. When analyzing only the exams done by the PG group, we found that 22.4% of 21,22 .…”
mentioning
confidence: 92%
“…A avaliação pré-operatória no âmbito ambulatorial, que inclui a consulta pré-anestésica, promove a identificação de riscos associados ao ato anestésico-cirúrgico, aumenta a chance de um resultado cirúrgico satisfatório, além de ser eficaz na redução da ansiedade pré-operatória 7 .…”
Section: Introductionunclassified
“…As complicações anestésicas podem ser classificadas como menores ou graves. São consideradas complicações anestésicas menores aquelas consideradas leves, que não causam danos ao paciente 6 . Exemplos de complicações menores são a dor de garganta, náuseas e vômitos moderados, lesão de dentes, gengivas ou lábios e tromboflebite 3,7 .…”
unclassified